Vinho Verde: um "vinho diferente" para a Europa e para o mundo - Cardoso, António Barros (2018)
We seek to understand the designation of these wines as "different wines" in light of the historical evolution of grapevine management systems in the current Demarcated Green Wine Region. The differences for other wines produced in Portugal, especially white wines, have been dwarfed by the technological evolution of the conditions of their production